2017
DOI: 10.4103/jispcd.jispcd_184_17
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 mutations in salivary pleomorphic adenoma and carcinoma-ex-pleomorphic adenoma

Abstract: Objectives:It is hypothesized that carcinoma-ex-pleomorphic adenoma (Ca-ex-PA) is malignant from the beginning or is a malignant transformation of a recurrent or a long-standing pleomorphic adenoma (PA). The accumulation of genetic instabilities is suggested to be the main reason for malignant transformation in PA. The aim of this study was to determine the prevalence of BRCA1/2 mutations in PA and Ca-ex-PA.Materials and Methods:A total of ninety salivary gland tumors (45 Ca ex-PA and 45 PA) were selected. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The BRCA1 gene is expressed in many tissues and organs, such as the breast, ovaries, testes, lymphocytes, brain and sigmoid colon. It was also detected in salivary glands and other regions of the oral cavity [40]. The BRCA1 protein plays an important role in maintaining genome integrity: it is involved in the control of transcription, the repair of DNA double-strand breaks, and cell cycle regulation [2].…”
Section: Discussionmentioning
confidence: 99%
“…The BRCA1 gene is expressed in many tissues and organs, such as the breast, ovaries, testes, lymphocytes, brain and sigmoid colon. It was also detected in salivary glands and other regions of the oral cavity [40]. The BRCA1 protein plays an important role in maintaining genome integrity: it is involved in the control of transcription, the repair of DNA double-strand breaks, and cell cycle regulation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenesis is a multistep process, and recent studies on molecular biology have indicated the genetic basis of the process of carcinogenesis. [ 63 121 ] Secretory leukocyte protease inhibitor (SLPI) has broad anti-microbial and anti-inflammatory properties and has been considered as a potential diagnostic and prognostic biomarker in head and neck cancer. Besides, SLPI protects against head and neck cancer development.…”
Section: Methodsmentioning
confidence: 99%
“…Also DNA repair proteins like BRCA1/2 are linked to treatment outcomes. [ 121 ] BRCA1/2 genes are involved in DNA repair in cancers such as breast cancer and ovarian cancer. A recent published work revealed the BRCA1/2 mutations in salivary gland tumors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor growth and metastasis are correlated to the function and the altered expression level of many proteins, as well as gene mutations (5,8,(22)(23)(24). In addition, cancer cell invasion and metastasis are correlated to the level of cancer cell differentiation.…”
Section: Introductionmentioning
confidence: 99%